The Effectiveness of Teacher Training on Environmental Education: Challenges and Strategy for Future Training Program - E. Eliyawati; Ari Widodo; Ida Kaniawati; Hiroki Fujii (Jurnal Penelitian Pendidikan IPA, 2023)
A professional teacher is a teacher who masters professional knowledge and skills. Increasing their professionalism is needed to achieve Sustainable Development Goals (SDGs). This research attempts to analyze the effectiveness of teacher training programs in environmental education that focus on identifying the challenges and strategy for the future training program. The research method was triangulation, combining quantitative and qualitative data analysis, including document analysis, questionnaire, and interview results. Sixty-five teachers with experience in environmental education were surveyed, and seven were interviewed. The results show that the sustainability context (environmental, economic, and sociocultural dimensions) needs to be embedded into environmental education teacher training. All training materials are currently oriented toward the environmental context. The provided training focuses on imparting knowledge on environmental education and has not yet expanded to include raising awareness or fostering sustainable action. As a result, future teacher programs must emphasize not only knowledge, but also awareness and action to attain sustainability. Schools and other relevant parties must fully support the rollout of the teacher-training initiative.